Fractional radiofrequency microneedling for skin rejuvenation. Issue 1 (11th March 2020) - Cook, Jonathan; Waughtel, Jessica; Lennox, Krystie P.; Pozner, Jason N.
Abstract: Patients continue to seek aesthetic procedures that treat intrinsic aging, progressive photodamage, skin laxity, and facial rhytids. Using the latest generation of radiofrequency microneedling (RFM) technology, it is possible to achieve elegant results when treating these concerns. In this article, we will discuss the mechanism of RFM, review the improvements in the latest generation of this technology, and consider applications of this device in aesthetic practice.